Perubahan Penggunaan Tanah dan Faktor Pendorongnya di Kabupaten Karimun - Rangga Olenka; Adrimas Adrimas; Melinda Noer (Jurnal Planologi, 2019)
ABSTRACTEarly detection is important to looking at the phenomenon of massive land use changes. Karimun Regency is one of the areas designated as one of the National Strategic Areas (KSN) for the benefit of economic growth. In addition, parts of the Karimun Regency are also designated as Free Trade Zone (FTZ). This has led to changes in land use patterns. This study analyzes changes in land use in Karimun Regency and its driving factors. Analysis of land use changes was carried out using land use map  and socio-economic data in 2008 - 2017. Methods of data analysis using spatial analysis and analysis of driving factors. The results showed that there were significant changes that occurred in land use. The rate of forest conversion and the decline in the area of agricultural land are very alarming. Growth of the built up area continues to increase. Development pattern of built area only concentrates on center of economic activity that already exists and also on transportation routes. Meanwhile the drivers of change in land use vary. Economic factors such as GRDP Karimun Regency and Investment and social factors such as urbanization and residents working in the primary sector drives land use change in Karimun Regency in 2008 – 2017. Key words: land use, land use change, driven factor ABSTRAKDeteksi dini penting dalam melihat fenomena perubahan penggunaan tanah yang masif. Kabupaten Karimun merupakan salah satu wilayah yang ditetapkan sebagai salah satu Kawasan Strategis Nasional (KSN) untuk kepentingan pertumbuhan ekonomi. Selain itu sebagian wilayah Kabupaten Karimun juga ditetapkan sebagai Kawasan Perdagangan Bebas dan Pelabuhan Bebas (Free Trade Zone). Hal tersebut mendorong perubahan pola penggunaan tanah. Studi ini menganalisis perubahan penggunaan tanah dan faktor pendorongnya yang terjadi di Kabupaten Karimun. Analisis perubahan penggunaan tanah dilakukan menggunakan peta penggunaan tanah dan data sosial ekonomi pada tahun 2008 - 2017. Metode analisis data menggunakan analisis spasial dan analisis faktor pendorong. Hasil penelitian menunjukkan bahwa ada perubahan signifikan yang terjadi pada penggunaan tanah. Laju konversi hutan sangat mengkhawatirkan. Pertumbuhan area terbangun terus meningkat. Pola pengembangan area terbangun hanya berkonsentrasi pada pusat kegiatan ekonomi yang sudah ada dan juga pada jalur transportasi. Sementara itu pendorong perubahan penggunaan tanah bervariasi. Faktor ekonomi seperti PDRB Kabupaten Karimun dan Investasi sedangkan faktor sosial seperti urbanisasi dan penduduk yang bekerja di sektor primer mendorong perubahan penggunaan tanah di Kabupaten Karimun tahun 2008 – 2017.  Kata Kunci: penggunaan tanah, perubahan penggunaan tanah, faktor pendorong.